2021
DOI: 10.1371/journal.pone.0260128
|View full text |Cite
|
Sign up to set email alerts
|

Interaction effect of coping self-efficacy and received support in daily life of hematopoietic cell transplant patient-caregiver dyads

Abstract: Objectives According to the social cognitive theory, social support and self-efficacy may interact with each other i.e. compete or account jointly for better adaptation. This study examined the nature of the interaction between coping self-efficacy and received social support in daily lives of patient-caregiver dyads after cancer treatment. We tested whether the effect of daily fluctuations in coping self-efficacy and received support on daily affect was synergistic (positive jointed effect), compensatory (pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…Several studies have supported the development of a deep and mutual relationship between the caregiver and the patient throughout the caregiving process, to the extent that the caregiver and the patient in uence each other's mental and physical health [39][40][41] and feel a sense of commitment to endure their current situation [34]. Our study showed a mutual relationship between the caregiver and the patient, as evidenced by their insistence on physical presence together.…”
Section: Discussionsupporting
confidence: 70%
“…Several studies have supported the development of a deep and mutual relationship between the caregiver and the patient throughout the caregiving process, to the extent that the caregiver and the patient in uence each other's mental and physical health [39][40][41] and feel a sense of commitment to endure their current situation [34]. Our study showed a mutual relationship between the caregiver and the patient, as evidenced by their insistence on physical presence together.…”
Section: Discussionsupporting
confidence: 70%
“…In practice, patients are withdrawn and unwilling to cooperate with medics. Kroemeke and Sobczyk-Kruszelnicka indicate that typical daily coping and the support received were significantly associated with a higher daily positive affect [42], which additionally strengthens the importance of research on social support in dyads during cancer. Taking account of, for example, existential aspects in experiencing a neoplastic could indicate important factors influencing the experience of multidimensional support in both patients and caregivers.…”
Section: Discussionmentioning
confidence: 60%
“…In practice, patients are withdrawn and unwilling to cooperate with medics. Kroemeke and Sobczyk-Kruszelnicka indicate that typical daily coping and the support received were significantly associated with a higher daily positive affect [ 42 ], which additionally strengthens the importance of research on social support in dyads during cancer.…”
Section: Discussionmentioning
confidence: 83%
“…believe that in many cases, the presence of an incurable disease impacts the caregiver–patient relationship and redefines it. 32 Several studies have supported the development of a deep and mutual relationship between the caregiver and the patient throughout the caregiving process to the extent that the caregiver and the patient influence each other's mental and physical health 39 , 40 , 41 and feel a sense of commitment to endure their current situation. 33 Our study showed a mutual relationship between caregivers and patients, as evidenced by their insistence on physical presence.…”
Section: Discussionmentioning
confidence: 99%